Analisis Yuridis Restrukturisasi Kredit Sindikasi Sebagai Akibat Hukum Terjadinya Corona Virus Disease 2019 (Covid-19) untuk Pembiayaan Pembangunan Jalan Tol - Zulfi Diane Zaini; Katleya Puspa Nagari (Jurnal Supremasi, 2023)
The policy arrangements for granting syndicated credit facilities to debtors and the process of implementing their restructuring as a legal consequence of the occurrence of Covid-19 for financing toll road construction are urgent to be researched. Through normative juridical research, it concluded that in policy arrangements for granting syndicated credit facilities to debtors, the bank providing the facility must be based on the bank's credit policy and must review it in advance so as not to exceed the Maximum Lending Limit (BPMK). The Bank applies a syndicated credit facility to minimize credit risk. The mechanism for implementing syndicated credit for toll road financing ended with the signing of an addendum credit agreement with related parties, including debtors, credit facility agents, and partner banks. Bank Lampung as Partner Bank conducts credit restructuring analysis and conducts pre-committee and committee meetings to make credit restructuring decisions.